Coffee protects cardiovascular health by maintaining the structure of coronary arterial wall intimal collagen - Susilawati, I Dewa Ayu Ayu; Suryono, Suryono; Purwanto, Purwanto; Burlakovs, Juris; Yaro, Abubakar (Coffee Science - ISSN 1984-3909, 2020)
This study aimed to determine whether coffee consumption affects the structure of coronary arterial wall and protects against coronary artery disease (CAD) in atherosclerotic rat model induced by periodontitis. Rats (n = 21) were divided into three groups (i) Coffee group (periodontitis + coffee), (ii) Periodontitis group (no coffee), and (iii) Control group (no periodontitis, no coffee). A single dose of coffee suspension (representing one cup) was given daily by stomach sondation to the rats in the coffee group. The experiment was conducted for 5 wk. At the completion of the experiment, all of rats were sacrificed. Their hearts containing coronary arteries were removed and analyzed by histochemistry assay. In addition, the serum level of collagen degrading enzymes matrix metalloproteinase–2 (MMP–2) was also analyzed using Enzyme–link immunosorbent assay (Elisa). Results demonstrated that coronary atherosclerotic lesions including atheroma, stenosis, and vascular occlusion were rarely identified in the coffee group. The coronary arterial wall demonstrated relatively symmetrical intima-media thickness (IMT) and the lumen diameter remained adequate for blood flow. The intimal collagen was intact, dense and thick. MMP–2 level was significantly lower (P < 0.05) in the coffee group. In conclusion, coffee maintained the structure of coronary arterial wall particularly the intimal collagen, providing protection against CAD. This might also mediate the vascular resistance against rupture and thrombosis that might precipitate the occurrence of acute coronary syndrome (ACS). Key words: Acute coronary syndrome (ACS); Coronary artery disease (CAD); Histochemistry; Intima-media thickness (IMT); Matrix metalloproinase-2 (MMP-2).